The effect of the electron screening in the d(3He,p)4He reaction in deuterated metals; Nucleus 2020. Nuclear physics and elementary particle physics. Nuclear physics technologies - Nurkin A. S. Azamat Serikbaevich; Bystritsky V. M. Vyacheslav Mikhaylovich; Dudkin G. N. Gennadiy Nikolaevich; Chumakov D. K. Daniil Kambarbekovich; Filipowicz M. Mariusz; Filippov A. V. Aleksandr Viktorovich; Nechaev B. A. Boris Aleksandrovich; Padalko V. N. Vladimir Nikolaevich; Penkov F. M. Fedor Mikhaylovich; Tuleushev Yu. Z. Yury Zhianshakhovich; Varlachev V. A. Valery Aleksandrovich; Zhakanbaev E. A. Eldar Askhatovich (2020, 2020)
Title screen